Time reduction of light curing: Influence on conversion degree and microhardness of orthodontic composites - Ferreira Amato, Patricia Alves; Martins, Renato Parsekian [UNESP]; Santos Cruz, Carlos Alberto dos [UNESP]; Capella, Marisa Veiga [UNESP]; Martins, Leandro [UNESP] (Elsevier B.V., 2014)
Introduction: The aim of this study was to assess the influence of curing time and power on the degree of conversion and surface microhardness of 3 orthodontic composites. Methods: One hundred eighty discs, 6 mm in diameter, were divided into 3 groups of 60 samples according to the composite used-Transbond XT (3M Unitek, Monrovia, Calif), Opal Bond MV (Ultradent, South Jordan, Utah), and Transbond Plus Color Change (3M Unitek)-and each group was further divided into 3 subgroups (n = 20). Five samples were used to measure conversion, and 15 were used to measure microhardness. A light-emitting diode curing unit with multiwavelength emission of broad light was used for curing at 3 power levels (530, 760, and 1520 mW) and 3 times (8.5, 6, and 3 seconds), always totaling 4.56 joules. Five specimens from each subgroup were ground and mixed with potassium bromide to produce 8-mm tablets to be compared with 5 others made similarly with the respective noncured composite. These were placed into a spectrometer, and software was used for analysis. A microhardness tester was used to take Knoop hardness (KHN) measurements in 15 discs of each subgroup. The data were analyzed with 2 analysis of variance tests at 2 levels. Results: Differences were found in the conversion degree of the composites cured at different times and powers (P < 0.01). The composites showed similar degrees of conversion when light cured at 8.5 seconds (80.7%) and 6 seconds (79.0%), but not at 3 seconds (75.0%). The conversion degrees of the composites were different, with group 3 (87.2%) higher than group 2 (83.5%), which was higher than group 1 (64.0%). Differences in microhardness were also found (P < 0.01), with lower microhardness at 8.5 seconds (35.2 KHN), but no difference was observed between 6 seconds (41.6 KHN) and 3 seconds (42.8 KHN). Group 3 had the highest surface microhardness (35.9 KHN) compared with group 2 (33.7 KHN) and group 1 (30.0 KHN). Conclusions: Curing time can be reduced up to 6 seconds by increasing the power, with a slight decrease in the degree of conversion at 3 seconds; the decrease has a positive effect on the surface microhardness.